2020
DOI: 10.32615/ps.2019.171
|View full text |Cite
|
Sign up to set email alerts
|

Special issue in honour of Prof. Reto J. Strasser - Analysis of drought response of sunflower inbred lines by chlorophyll a fluorescence induction kinetics

Abstract: The aim of the study was to screen nine inbred lines of sunflower by inducing drought for 10 d and subsequent rewatering for 5 d. Impact of drought was determined by chlorophyll fluorescence and some physiological parameters. Drought led to a decrease in the photosynthetic performance, the quantum yield, and efficiency of electron transport in sunflower lines, while it caused an increase in the absorption flux per reaction centre, dissipation of an active reaction centre, and K-band as well as L-band. Drought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…This statement can be supported by the findings of Flexas et al (2009), who demonstrated that the reduction in leaf RWC due to drought stress caused an imbalance in captured photon energy by PSII and its utilisation in CO 2 reduction, which resulted in electron transfer to molecular oxygen (O 2 ) forming ROS that destroy the thylakoidal membrane protein complexes. Thus, the differential tolerance to drought stress in mung bean cultivars can be related to their better ability to protect the photosynthetic apparatus as observed in several crops (Ogbaga et al, 2020), for example, wheat (Zivcak et al, 2009), sesame (Boureima et al, 2012), sunflower (Arslan et al, 2020). In contrast, Lawlor and Tezara (2009) argued that solar energy absorption, energy transfer from the antenna to the reaction centre, charge separation or electron transfer from the reaction centre to pheophytin and Q A occur Note: All the measurements are deduced from the OJIP transients conducted on the fully expanded third leaf from the shoot apex of the potted plants (mean ± SE; n = 10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This statement can be supported by the findings of Flexas et al (2009), who demonstrated that the reduction in leaf RWC due to drought stress caused an imbalance in captured photon energy by PSII and its utilisation in CO 2 reduction, which resulted in electron transfer to molecular oxygen (O 2 ) forming ROS that destroy the thylakoidal membrane protein complexes. Thus, the differential tolerance to drought stress in mung bean cultivars can be related to their better ability to protect the photosynthetic apparatus as observed in several crops (Ogbaga et al, 2020), for example, wheat (Zivcak et al, 2009), sesame (Boureima et al, 2012), sunflower (Arslan et al, 2020). In contrast, Lawlor and Tezara (2009) argued that solar energy absorption, energy transfer from the antenna to the reaction centre, charge separation or electron transfer from the reaction centre to pheophytin and Q A occur Note: All the measurements are deduced from the OJIP transients conducted on the fully expanded third leaf from the shoot apex of the potted plants (mean ± SE; n = 10).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, JIP‐test was also performed following Strasser et al (2000). Several researchers proposed that JIP‐test parameters can be used as potential indicators of structural disorders in PSII and intersystem electron carriers (Arslan et al, 2020; Kalaji et al, 2016). The QYs of primary photochemistry or charge separation (ΦP o ) and the electron transfer from QA to PQ (ΦE o ) did not change in the drought‐tolerant cultivar cv.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the appearance of K-band suggested that drought in the leaves of “Golden Delicious Reinders” caused an inactivation of the OEC, while cultivar “Crvenka” retained a stable OEC (negative K band). L and K-bands with positive amplitudes were previously recorded for passion fruit [ 38 ] and sunflower [ 39 ] when exposed to drought. Drought significantly affected all the photosynthetic parameters studied in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, they are considered indicators of light use efficiency and production capacity (Croft et al, 2017). The reduction of photosystem II (PSII) photochemical activity is indicative of sensitivity to stress (Arslan et al, 2020). The majority of sunflower varieties maintain chlorophyll a and b levels in drought conditions.…”
Section: Photosynthetic Pigmentsmentioning
confidence: 99%
“…Recent environmental fluctuations have reduced rainfall, particularly in arid and semiarid areas, thus generating stress in plants, namely stunted plant growth, physiology, and yield. Reduced crop yield under low water availability is associated with metabolic variations in plants (Ali et al, 2020;Arslan et al, 2020). To resolve this issue, drought-tolerant crops are grown in the affected areas.…”
Section: Introductionmentioning
confidence: 99%